Implementasi Pemberhentian Tidak Dengan Hormat Terhadap Anggota Kepolisian di Lingkungan Wilayah Hukum Kepolisian Daerah Riau yang Melakukan Desersi Berdasarkan Peraturan Pemerintah Nomor 1 Tahun 2003 Tentang Pemberhentian Anggota Kepolisian Negara Republ - Rusjaidi, Ananda Rizky; Asnawi, Eddy; Oktapani, Silm (Peneliti.net, 2025)
This study examines the implementation of dishonorable discharge for police officers who committed desertion in the Riau Regional Police jurisdiction based on Government Regulation Number 1 of 2003. Using socio-legal research methods through interviews and document analysis, the study found that the implementation has not been optimal, evidenced by the absence of dishonorable discharge recommendations in 2022-2023 cases. Several factors hamper implementation, including limited human resources and budget, non-compliance of perpetrators, human rights considerations, and technical constraints. The research suggests that improvement efforts are needed, including personnel additions according to staffing requirements, enhanced inter-agency coordination, stricter sanctions for repeat offenders, and optimization of budget and examination techniques. The study concludes that the Riau Regional Police needs to be more assertive in implementing dishonorable discharge for repeat desertion offenders while encouraging deserters to uphold their commitment not to repeat violations and demonstrate behavioral improvement.